Comparison of the performance of risk scoring systems for tumor bleeding in patients with inoperable gastric cancer - Kim, Young-Il; Choi, Il Ju; Lee, Jong Yeul; Kim, Chan Gyoo; Kim, Hark Kyun; Park, Young Lee (Endoscopy, 2020)
Background The Glasgow – Blatchford bleeding score (GBS) and admission and full Rockall scores are widely used risk scoring systems to stratify risk and determine the need for intervention in patients with upper gastrointestinal bleeding. We evaluated the performance of these risk scoring systems in patients with gastric cancer and tumor bleeding.Methods This retrospective study included patients with inoperable gastric cancer who presented with tumor bleeding at the National Cancer Center, Korea, between 2001 and 2015. The GBS, and admission and full Rockall scores were calculated. Primary outcome was the performance of the risk scoring systems in predicting the need for urgent interventions (endoscopic therapy, transarterial embolization, and surgery). The risk factors associated with urgent intervention were analyzed.Results Of 357 patients with tumor bleeding, 118 (33.1 %; 116 endoscopic therapy, 2 trans-arterial embolization) required urgent intervention. The full Rockall score was better at predicting the need for urgent intervention (area under the receiver operating characteristic curve = 0.78; P < 0.001) than the GBS (0.56) and admission Rockall score (0.56). Hemostatic intervention was not performed in patients with a full Rockall score ≤ 6 (103 patients, 28.9 %). On multivariate analysis, endoscopic stigmata of recent hemorrhage of Forrest classes Ia – IIb were significant factors associated with urgent intervention.Conclusions The full Rockall score was superior to the GBS and admission Rockall score in predicting the need for urgent intervention for tumor bleeding. Thus, endoscopic evaluation is required to determine the need for urgent intervention in patients with gastric cancer and tumor bleeding.